Inhibition of macrophage migration by muramyl peptides. - Nagao, S (1979)
In the capillary tube migration system a synthetic muramyl dipeptide (MDP; N-acetylmuramyl-L-alanyl-D-isoglutamine), a part of bacterial cell wall peptidoglycans, inhibited the migration of peritoneal exudate macrophages from normal guinea pigs or rats. The migration inhibition was also caused by some MDP-containing peptidoglycan fragments from cell walls of Lactobacillus plantarum and Staphylococcus epidermidis. The migration inhibition could not be explained on the basis of macrophage migration inhibitory factor. A stereochemically highly specific structure of MDP required for its adjuvant activity was also required for the macrophage migration inhibition. These findings suggest that MDP and MDP-containing cell wall fragments may activate macrophages and that this activation may be important in the exertion of their adjuvant activity.